Zakat dan Jizyah Sebagai Pengendali Sistem Moneter: Sebuah Kajian Konseptual - Wahyu Nugroho Nugroho; Syamsuri Syamsuri,; Syamsuddin Arif Arif; Dzul Fadli Fadli (Islamic Economics Journal, 2019)
availability through the role it's government, so it can maintain the welfare of it's people. The government is free to determine the state’s income policy, which must be fair and not violate sharia. Among the state income policies in Islam are zakat and jizya. Zakat is imposed on Muslims, while jizya is on non-Muslims. History records that both can influence the monetary economy in Muslim countries. Principally, these two are not the same. So, the reson for this research is to find the concept of both is monetary controllers. This research uses qualitative method of historical approach, by using past data to understand the events that took placeat the moment. The concept of zakat is worship for Muslims to get closer to God and purify the wealth. Meanwhile, jizya is required from non-Muslims as a form of obedience to the government which guarantees their lives in an Islamic state. Moreover both can affect state's monetary. Because when a Muslim pays zakat, it will increase wealth distribution (aggregate demand), as a result, the recipient becomes prosperous, with the assumption that they will invest. This investment will shift the demand for money (aggregate supply) so that the number of goods and services also grow. Meanwhile, jizya is distributed to government operations including security, so that security can also increase public confidence in carrying out real economic activities. Therefore, if zakat and jizya are managed properly, they will keep inflation down. Moreover, it can even eliminate the economic crisis and improve people’s welfare.